Islamic Cultural Influence on Characters’ Interaction in Khaled Hosseini’s "And the Mountain Echoed" - Pamungkas, Amalia Chairunnisa; Ruly Indra Darmawan (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study focuses on analyzing the Islamic culture and its influence on the characters in the novel. The novel’s main background story takes place in Afghanistan, where Islam is deeply rooted in the society. The rooted belief in Islam shaped the culture of the Afghans. Through the lens of Clifford Geertz's theory of “Religion as Cultural System,” he observes that the practice of a culture often follows the teachings of a religion in the area. This analysis also draws on the opinions of some Islamic figures as a supporting theory to define the Islamic culture portrayed in the novel. This study found that Islamic cultures are portrayed in some chapters of the novel. Moreover, the results of this analysis provide evidence that Islam in Afghanistan significantly influences the country's culture. Since the religion is rooted in Afghanistan, some cultural values follow the belief of Islam found in the characters' daily interactions. They demonstrate how women should wear hijab, how Muslims perform their worship prayers, how a family stays connected, and how younger people should interact with older individuals.